2022
DOI: 10.1155/2022/2615753
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Carbapenem-Resistant Klebsiella pneumoniae in a Tertiary Hospital in Northern China

Abstract: Background. In recent years, carbapenem-resistant Klebsiella pneumoniae (CRKP) has emerged rapidly in China with the abuse and overuse of antibiotics, and infections caused by CRKP pose a serious threat to global public health safety. The present study aimed to explore the epidemiological characteristics of CRKP isolates in Northern China and to elucidate their drug resistance mechanisms. Methods. 45 CRKP strains were consecutively collected at a teaching hospital from March 1st, 2018 to June 30th, 2018. Antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…This is consistent with earlier studies [17,45,46] and suggests that it is endemic to this region. A study from China observed that among bla CTX-M producers, bla CTX-M-2 was the most prevalent genotype (44/45, 97.8%), followed by bla CTX-M-3 (20/45, 44.4%), bla CTX-M-1 (18/45, 40%), bla CTX-M-9 (17/45, 37.8%), and bla CTX-M-15 (5/45, 11.1%) [47]. According to a study from Tanzania, ESBL genes were distributed as follows: 29/32 (90.6%) had bla CTX-M-15 , two had bla SHV-12 , and one had both bla CTX-M-15 and bla SHV-12 .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with earlier studies [17,45,46] and suggests that it is endemic to this region. A study from China observed that among bla CTX-M producers, bla CTX-M-2 was the most prevalent genotype (44/45, 97.8%), followed by bla CTX-M-3 (20/45, 44.4%), bla CTX-M-1 (18/45, 40%), bla CTX-M-9 (17/45, 37.8%), and bla CTX-M-15 (5/45, 11.1%) [47]. According to a study from Tanzania, ESBL genes were distributed as follows: 29/32 (90.6%) had bla CTX-M-15 , two had bla SHV-12 , and one had both bla CTX-M-15 and bla SHV-12 .…”
Section: Discussionmentioning
confidence: 99%